Hajdú-Bihar megyei élelmiszer-gazdasági vezetők elvárásainak vizsgálata - Juhász, Csilla (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
The main aim of my essay is to examine and introduce the expectance motivational characteristics, problems and opportunities of food-economic leaders in Hajdú-Bihar County. I am studying an expectancy of leaders in agriculture and food industry. Based on my research, I have drawn the following conclusions I made a questionnaire for researching it. The questionnaire contained some expectancy factors. I made some group from leaders about their age, sex, managerial level, and their skills. In my studies I found, that the most important expectancy possibility is the good prob-lem solving skills. Managers do not expect the informatics skills; they do not expect good communications skills surprisingly. About managers’ opinions the less important expectancy factor is language knowledge.